ПЕДАГОГИК РАСМНИНГ ТАСВИРИЙ САНЪАТ ДАРСЛАРИДАГИ АҲАМИЯТИ - Бекмуратов, Т.; Қўчқоров, Д. (SCIENCE and SOCIETY, 2020)
The article gives an overview of the advantages of teaching drawing to students in pedagogical painting. It also provides information on how to draw the view of the object in an appropriate way and the rules and regulations of the depicting process.
Keywords: pedagogical painting; pencil hatching; lighting; ellipse; layout; constructional structure; ball shape; perspective; spectral colors; objective image